IMPACT OF EMOTIONAL INTELLIGENCE ON PROJECT MANAGER’S COMPETENCY - Myneni, Kranti Kumar; A, Amrutha (International Journal of Engineering Science Technologies, 2023)
There is increased awareness about the factors that affect project success since project stakeholders are constantly working towards a successful project. Although there are many aspects that affect a project's success, project managers are essential. The purpose of this study is to investigate how emotional intelligence (EI) affects project managers' ability to manage projects effectively. Research has been done in fields of relation between emotional intelligence and project success, but influence of emotional intelligence on project manager’s competency in the field is unknown. In this study linear regression is applied to determine the inter relation between emotional intelligence and competency of a project manager. The practical application of linear regression was demonstrated and conclusions were drawn from the findings of the study. The inter-relations between emotional intelligence and competency of project managers are determined along with the degree of dependency. It is important to understand the dependency of competency on soft skills to enhance a project manager’s performance and thus the project’s success.